Urban expand on agricultural lands and the problems that result from it in Al- Ghraat Regions - قاسم هادي صفاقس (Al-Adab Journal, 2018)
The Urban expand is urban problem that cities suffer from .It is considered more changing reasons for the investment of the land. This change is appeared in area which is devoted for agricultural usage. This can be shown in Al- Ghraat region which is followed to Al-Adhamyia province in the North of Baghdad .It is agricultural area where all the constituents are available (natural and human) However , during the comparison between usages from( 1995-2016) we can see very clear shortage of agricultural usage very clear shortage of agricultural usage compares with residential ( housing) usage and its horizontal expand at the expense of the agricultural land and that lead to many urban problems like, look of services (water, electricity , sewage) as well as lack of basic structures ( medication) and pollution. This expand is a result from the loss of laws that prevent the overtaking and also the political conditions and crisis’s which are passed in Iraq.